Why have interest rates fallen far below the return on capital - Magali Marx; Benoît Mojon; François R. Velde (Federal Reserve Bank of Chicago, 2018)
Risk-free rates have been falling since the 1980s while the return on capital has not. We analyze these trends in a calibrated OLG model with recursive preferences, designed to encompass many of the "usual suspects" cited in the debate on secular stagnation. Declining labor force and productivity growth imply a limited decline in real interest rates and deleveraging cannot account for the joint decline in the risk free rate and increase in the risk premium. If we allow for a change in the (perceived) risk to productivity growth to fit the data, we find that the decline in the risk-free rate requires an increase in the borrowing capacity of the indebted agents in the model, consistent with the increase in the sum of public and private debt since the crisis, but at odds with a deleveraging-based explanation put forth in Eggertsson and Krugman (2012).
Keywords: 330; Zins; Kapitaleinkommen; Risikoprämie; USA; EU-Staaten; Japan